2004
DOI: 10.1111/j.1365-2249.2004.02496.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal anti-HPA-1a antibodies and polyclonal IVIG on the activation status of vascular endothelial cells

Abstract: SUMMARYMaternal anti-HPA-1a antibodies can cause severe fetal and neonatal alloimmune thrombocytopenia (FNAIT), complicated by intracranial haemorrhage (ICH). Antenatal treatment with maternal intravenous immunoglobulin (IVIG) seems to protect against ICH even when thrombocytopenia persists. The aim of this study was to investigate if anti-HPA-1a antibodies and IVIG potentially affect vascular endothelial cells (ECs) in order to identify susceptibility for ICH. Human umbilical cord endothelial cells (HUVEC) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…In addition, HPA‐1a antibodies might have an effect on endothelial cells αVβ3. Although CamTran007 does not lead to endothelial cell activation in a static in vitro system, 33 it does inhibit binding of transfectant cells expressing αVβ3 Leu‐33 to fibrinogen 28 . Results from studies that assess the effect on the interaction between endothelial cells, granulocytes, and PLTs in flowing blood are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HPA‐1a antibodies might have an effect on endothelial cells αVβ3. Although CamTran007 does not lead to endothelial cell activation in a static in vitro system, 33 it does inhibit binding of transfectant cells expressing αVβ3 Leu‐33 to fibrinogen 28 . Results from studies that assess the effect on the interaction between endothelial cells, granulocytes, and PLTs in flowing blood are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This improved neonatal course is likely to be, in part, the result Another main factor is, obviously, awareness of the diagnosis, with the opportunity to have matched platelets ready at delivery. In addition, we have to stress that IVIG likely acts in multiple ways in the prevention of ICH, such as through not yet completely clear protective effects on the endothelium [23]. More insight in these mechanisms is needed to determine the optimal use of IVIG in the antenatal and postnatal prevention of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of safety, we have already shown that the B2 series of antibodies have no significant adverse effects on platelet activation and function (50). HPA-1a antibodies also bind to endothelial cells αvβ3, but there is published evidence that B2G1 does not alter endothelial cell growth and activation status (51). Moreover, we have shown that ligand binding to αvβ3 is unaffected in the presence of B2G1 (C. Ghevaert, unpublished observations).…”
Section: Figurementioning
confidence: 92%